Electrosynthesis of poly(2, 5-dimercapto-1, 3, 4-thiadiazole) films and their composites with gold nanoparticles at a polarised liquid|liquid interface. (20th August 2022) - Suárez-Herrera, Marco F.; Gamero-Quijano, Alonso; Scanlon, Micheál D.
Abstract: The organosulfur compound 2, 5-dimercapto-1, 3, 4-thiadiazole (DMcT) finds widespread applications in batteries, lubricant fluids, heavy metal ion sensors, waste-water purification and as a biocide. In this article, we demonstrate the untapped versatility inherent to using biphasic systems for electrosynthesis by showcasing several successful approaches to the electrosynthesis of poly(DMcT) films at a polarised interface between two immiscible electrolyte solutions (ITIES) by cyclic voltammetry (CV) cycling using either I2, Hg 2+ or O2 as the oxidising agents. AC voltammetry is demonstrated as an effective in situ method to monitor poly(DMcT) film formation by I2 or Hg 2+ as a function of the aqueous electrolyte anion and pH. DMcT is further shown to act as a binder molecule to promote interfacial gold nanoparticle (AuNP) assembly into floating films at an immiscible liquid|liquid (L|L) interface. Exploiting the electrocatalysis of DMcT oxidation by O2 in the presence of adsorbed interfacial AuNPs yields AuNP/poly(DMcT) composite films. Raman spectroscopy suggests the latter were a coordination polymer of poly(DMcT) with AuNPs and surface enhanced Raman spectroscopy (SERS) active. The dielectric nature of the poly(DMcT) films suppresses the capacitance at the ITIES, yet the AuNP/poly(DMcT) films show a very high interfacial capacitance, with an ability to efficiently adsorb cations. Thus, these films open opportunities to selectively modulate the interfacial capacitance, potentially forming the basis of novel "soft" capacitors at a polarised L|L interface.